The spatiotemporal profile of Dendrobium huoshanense and functional identification of bHLH genes under exogenous MeJA using comparative transcriptomics and genomics - He, Xiaomei; Zhang, Wenwu; Sabir, Irfan Ali; Jiao, Chunyan; Li, Guohui; Wang, Yan; Zhu, Fucheng; Dai, Jun; Liu, Longyun; Chen, Cunwu; Zhang, Yingyu; Song, Cheng (Frontiers in Plant Science, 2023)
Introduction Alkaloids are one of the main medicinal components of Dendrobium species. Dendrobium alkaloids are mainly composed of terpene alkaloids. Jasmonic acid (JA) induce the biosynthesis of such alkaloids, mainly by enhancing the expression of JA-responsive genes to increase plant resistance and increase the content of alkaloids. Many JA-responsive genes are the target genes of bHLH transcription factors (TFs), especially the MYC2 transcription factor. Methods In this study, the differentially expressed genes involved in the JA signaling pathway were screened out from Dendrobium huoshanense using comparative transcriptomics approaches, revealing the critical roles of basic helix-loop-helix (bHLH) family, particularly the MYC2 subfamily. Results and discussion Microsynteny-based comparative genomics demonstrated that whole genome duplication (WGD) and segmental duplication events drove bHLH genes expansion and functional divergence. Tandem duplication accelerated the generation of bHLH paralogs. Multiple sequence alignments showed that all bHLH proteins included bHLH-zip and ACT-like conserved domains. The MYC2 subfamily had a typical bHLH-MYC_N domain. The phylogenetic tree revealed the classification and putative roles of bHLHs. The analysis of cis-acting elements revealed that promoter of the majority of bHLH genes contain multiple regulatory elements relevant to light response, hormone responses, and abiotic stresses, and the bHLH genes could be activated by binding these elements. The expression profiling and qRT-PCR results indicated that bHLH subgroups IIIe and IIId may have an antagonistic role in JA-mediated expression of stress-related genes. DhbHLH20 and DhbHLH21 were considered to be the positive regulators in the early response of JA signaling, while DhbHLH24 and DhbHLH25 might be the negative regulators. Our findings may provide a practical reference for the functional study of DhbHLH genes and the regulation of secondary metabolites.